Pulmonary hypertension associated with sarcoidosis: mechanisms, haemodynamics and prognosis. Issue 1 (14th October 2005) - Nunes, H; Humbert, M; Capron, F; Brauner, M; Sitbon, O; Battesti, J-P; Simonneau, G; Valeyre, D
Abstract : Background: Pulmonary hypertension (PH) is a rare complication of sarcoidosis, although it is not uncommon in advanced disease. Methods: A retrospective series of 22 sarcoidosis patients (16 men) of mean (SD) age 46 (13) years with PH was divided into two groups depending on the absence (stage 0: n = 2, stage II: n = 4, stage III: n = 1) or presence (n = 15) of radiographic pulmonary fibrosis at the time of PH diagnosis. Results: In both groups PH was moderate to severe and there was no response to acute vasodilator challenge. In non-fibrotic cases no other cause of PH was found, suggesting a specific sarcoidosis vasculopathy, although no histological specimens were available. In cases with fibrosis there was no correlation between haemodynamics and lung volumes or arterial oxygen tensions, suggesting other mechanisms for PH in addition to pulmonary destruction and hypoxaemia. These included extrinsic arterial compression by lymphadenopathies in three cases and histologically proven pulmonary veno-occlusive disease in the five patients who underwent lung transplantation. Ten patients received high doses of oral prednisone for PH (stage 0: n  =  1, stage II: n  =  4 and stage IV: n  =  5); three patients without pulmonary fibrosis experienced a sustained haemodynamic response. Survival of the overall population was poor (59% at 5 years). Mortality was associated with NYHA functional class IV but not with haemodynamic parameters or with lung function. Conclusion: Two very different phenotypes of sarcoidosis combined with PH are observed depending on the presence or absence of pulmonary fibrosis. PH is a severe complication of sarcoidosis.